Chaperone-like activities of the two pre-incubated small heat shock proteins of Bombyx mori (Bangladesh Journal of Animal Science, 2018)
The important small heat shock proteins (sHSPs) of Bombyx mori sHSP19.9, sHSP20.1, sHSP20.4, sHSP20.8, sHSP21.4 and sHSP23.7 are known to display distinct chaperone like activity (CLA) against a range of non-native protein aggregation during environmental stress. The small heat shock proteins sHSP19.9 and sHSP20.8 are identical polypeptides containing a single Cys residue: Cys-43 and Cys-123 respectively. The current information proposes that sHSPs function to prevent irreversible aggregation sometimes pre-incubation is pre-requisite to enhance their chaperone activities. In an attempt to determine their function, we have examined whether these two proteins have CLA using pre-incubation chaperone assay. The assay was conducted against the aggregation of a non-native protein, bovine liver catalase (BLC), which is readily aggregated at 60° C. Heat induced aggregation of BLC was decreased from 100 to 17% in the presence of pre-incubated sHSP20.8, which was 60% for without pre-incubation at a 1:0.5 molar ratio of BLC to sHSP. Whereas the aggregation was decreased from 100 to 33% in the presence of sHSP19.9 with dithiothreitol (DTT) , which was 67% for without pre-incubation at a 1:0.25 molar ratio of BLC to sHSP. The functional reason for such variation might be due to the position of Cys residue in the amino acid sequence.Bang. J. Anim. Sci. 2017. 46 (4): 258-265